MODELING OF LARGE FAULTS IN ZONES OF LITHOSPHERIC EXTENSION AND NUMERICAL CONSTRAINTS ON DEFORMATION - Sherman S.I.; Cheremnykh A.V.; Bornyakov S.A.; Shishkina L.P. (My University, 2001)
A similarity-based physical model of faulting in zones of lithospheric extension simulated formation of fault systems in extended viscoelastic ductile material and their gradual coalescence into a single major suture. This process includes several stages that are marked by specific structural reorganization in fault systems and recorded in variations of their parameters (density, length, fractal dimensions, etc.). Structural reorganizations are evident in plots showing variations in fractal dimensions of fault systems, longest suture lengths, and fault density associated with deformation increase. The fractal dimensions of fault systems correlate with deformation, and their contrasting changes correspond to structural reorganizations. In nature, the fractal dimensions of fault systems can be easily estimated from the known hierarchy of faults, which allows further estimation of the relative degree of deformation and the structural evolution stage of major fault zones.